Topics in random matrix theory - Tao, terence (Hyderabad (India) Universities press, 2012)
The field of random matrix theory has seen an explosion of activity in recent years, with connections to many areas of mathematics and physics. However, this makes the current state of the field almost too large to survey in a single book. In this graduate text, we focus on one specific sector of the field, namely the spectral distribution of random Wigner matrix ensembles (such as the Gaussian Unitary Ensemble), as well as iid matrix ensembles.
Keywords: Random matrices; Matrices Sign pattern matrices; Linear and multilinear algebra